Organizing comittee - Mouzouropoulos, Theseas (My University, 2026)
As part of the organizing committee, I was responsible for the complete redesign of the conference identity, the design of the main promo event poster as well as the social media adaptations of the visual concept The concept of the poster for the 5th International Conference of Semiotics of Culture and Visual Communication is based on having two sign systems juxtaposed together for communication: the Morse Code language and the Textual language. Having in mind the main theme of the conference “Otherness”, the Morse Code plays the role of the alternative, the “other” language.